(untitled) (Journal of Hama University, 2026)
Introduction: The use of conventional impression techniques for the fabrication of complete removable dentures has shown satisfactory outcomes in most patients, despite certain inherent limitations. Recent advancements have led to the development of newer impression methods that eliminate the need for traditional impression materials by employing intraoral scanners (IOS). However, concerns have been raised regarding their applicability in digitizing edentulous arches. Consequently, clinical evaluation has become essential to analyze these techniques and determine their potential use in the field of complete removable prosthodontics. Purpose: This study aimed to investigate the dimensional accuracy of final impressions taken using the conventional technique with zinc oxide eugenol (ZOE) material compared to those obtained using an intraoral scanner, for the fabrication of complete removable maxillary dentures in completely edentulous patients. Materials and methods: The study sample consisted of eight completely edentulous maxillary patients, aged between 48 and 70 years (5 males and 3 females). For each patient, a final conventional impression was taken. A custom perforated tray was fabricated with specific perforations at the designated measurement points. This tray was placed on the final cast to mark the reference points for dimensional assessment. The tray was then inserted into the patient’s mouth, and the points were marked intraorally using methylene blue and a condenser. Following the removal of the tray, a digital final impression was obtained using the MEDET I600 intraoral scanner. The scanned impressions, with the reference points clearly visible, were analyzed on a computer using Blender software to perform the necessary measurements. Additionally, intraoral measurements between the alveolar ridge reference points were taken using a digital caliper. Results: The findings revealed statistically significant paired differences between the mean measurements obtained using the intraoral scanner and the corresponding intraoral measurements (in millimeters) across the study sample, regardless of the distance evaluated—except for the distance between the points located posterior to the palatal rugae and anterior to the posterior palatal seal, where no statistically significant differences were observed. In contrast, when using the conventional technique, there were no statistically significant differences between the mean measurements taken on the final cast and the intraoral measurements (in millimeters) for any of the evaluated distances. This was determined at a significance level of p < 0.05, corresponding to a 95% confidence level. Conclusion: Conventional impressions remain the most accurate method for completely edentulous cases. Intraoral scanners are currently less effective in capturing soft tissue details. They may be considered more suitable for partially edentulous cases or when natural teeth are present. Their application in fully edentulous situations could become more feasible with further advancements in scanning algorithms and software.